Comparing the diagnostic accuracy of ultrasound in the community and in the hospital setting for urinary calculi: A retrospective cohort study. (March 2017) - Westergreen-Thorne, Mathew; Lee, Sook Yan; Babawale, Kunle; Lovegrove, Catherine; Brewer, John; Shrotri, Nitin
Objective: The objective of this article is to test whether there is a significant difference in diagnostic accuracy between hospital and community-based ultrasound (US) for the detection of urinary calculi in the United Kingdom (UK). Materials and methods: A 30-month, single-blind, retrospective cohort study of all patients referred to Kent and Canterbury Hospital urology multidisciplinary meeting for suspected urinary calculi was conducted. Only those investigated with US and non-contrast computed tomography (NCCT, the gold standard) for their calculi were included. Concordance of US and NCCT was stratified by US location: i.e. either the hospital or community setting (e.g. the latter via general practitioners (GPs) or independent radiographers). Fisher's exact test was subsequently utilised to test for any significant difference between these two patient groups. Results: Of 2464 patients referred, 257 had both ultrasound and NCCT in their diagnostic workup. Of these, 150 and 107 patients had their US performed in hospital and community settings, respectively. No significant difference in the accuracy of US was detected between the two groups for the detection of urinary calculi when compared with NCCT. Conclusion: US carried out by independent radiographers and GPs in the community is just as accurate as US carried out by hospital sonographers for the detection of urinary calculi in the UK. Greater use of community US for the diagnosis of urinary calculi may promote greater patient/GP satisfaction and reduce hospital attendance without loss of diagnostic accuracy.